Elevated Serum FGG Levels Prognosticate and Promote the Disease Progression in Prostate Cancer - Peng, H. H.; Wang, J. N.; Xiao, L. F.; Yan, M.; Chen, S. P.; Wang, L.; Yang, K. (Frontiers in Genetics, 2021)
Castration-resistant prostate cancer (CRPC) threatens the health of men in general and no effective therapeutics currently exists for the treatment of CRPC. It is therefore of great importance to find a novel molecule that can be a biomarker and a therapeutic target for CRPC. First, we found that the serum fibrinogen gamma (FGG) levels in patients with CRPC were significantly higher than those with localized prostate cancer (PCa) through iTRAQ proteomics and ELISA experiments. Immunohistochemistry, quantitative real-time polymerase chain reaction and western blot also showed an increase of FGG expression in CRPC tissues and cells. Then we proved the proliferation, invasion and migration ability of CRPC cells were significantly reduced after FGG knockdown. The number of apoptotic cells increased at least sixfold after FGG silencing, and was observed in conjunction with an upregulation of p53, caspase 3, clea-caspase 3, and Bax, and a downregulation of Bcl2 and survivin. FGG knockdown in DU145 cells resulted in smaller xenografts than control cells in a mouse model. and we established that FGG is modulated by IL-6 which was increased in CRPC patients via phosphorylation of STAT3. The data suggests that FGG may be a potential therapeutic target and prognostic marker for CRPC.